Correctable biliary atresia and cholangiocarcinoma: a case report of a 63-year-old patient - Masaki Nio; Motoshi Wada; Hideyuki Sasaki; Hiromu Tanaka; Masatoshi Hashimoto; Yudai Nakajima (Surgical Case Reports)
Abstract Background Although cancer occurrence following surgery for biliary atresia has gradually increased, the development of cholangiocarcinoma in a native liver survivor of biliary atresia is extremely rare. Case presentation A 3-month-old female patient with the correctable type of biliary atresia underwent a cystoduodenostomy. At 16 years of age, she underwent multiple surgeries including lysis of intestinal adhesions, ileostomy, and gastrojejunostomy at another hospital. At 54 years of age, she underwent lithotomy at the porta hepatis, resection of the residual cystic bile duct with gallbladder, and hepaticojejunostomy in Roux-en-Y fashion. As she approached the age of 63, her computed tomography scan showed no liver tumors. In the following year, she developed cholangiocarcinoma at the porta hepatis and underwent chemotherapy. However, the cancer progressed, and she died before she reached the age of 64 years. Conclusions Cholangiocarcinoma is extremely rare in patients with biliary atresia. However, physicians should follow up patients with biliary atresia as closely as possible, as malignant tumors secondary to biliary atresia may increase in number in the near future because of the growing number of long-term survivors with biliary atresia.